Solitary confinement in atomically thin semiconductors - Leong, Boon Huat (Nanyang Technological University, 2023)
Electrons are often confined using electrostatically defined gates to form quantum dots (QDs). However, naturally occurring TMDCs may possess intrinsic defects that could lead to the formation of inhomogeneous disordered potential throughout the material. This may lead to less efficient electrostatic control of QDs which its success is crucial in contributing to the success of quantum computing.